Re-Engineering The Business Process of Slickline and Electric Line Operation - Putra, Rendi Harun; Cahyo, Winda Nur; Zhang, Tieling (Universitas Ahmad Dahlan, 2022)
A strategy to save cost related to oil exploration process is discussed in this paper. The focus is to reduce the cost in slickline and electric line operation in order to maintain the business continuity, where this conclusion was obtained by looking at the comparison between the costs incurred during previous operations with the costs incurred at this time by comparing the results of operations obtained as well as comparisons with oil and gas prices both before and after 2018. This concrete step to be taken is a method for lean management because there is a cost suppression in it. The context of its implementation is through Business Process Re-engineering which of course will implement appropriate method steps to be taken. The method steps taken are to implement Value Stream Mapping which in its preparation includes an analysis of the slickline and electric line operation work steps carried out, including by compiling; Product family or operation work steps, Current state map of both operations and Design future state map of Wire Line operation proposal and 5S theory process as completeness. The proposed strategy enable to reduce costs by combining slickline and electric line operations in one unit or one service company, then reducing the number of workers involved and making work more efficient, by reducing the Rig up and Rig process, Down PCE (Pressure Control Equipment), reducing the repetition of the work intervention process.